Preoperative CHA2DS2-VASc Score Predicts Postoperative Atrial Fibrillation after Lobectomy - Lee, Charles T.; Strauss, David M.; Stone, Lauren E.; Stoltzfus, Jill C.; Puc, Matthew M.; Burfeind, William R. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Postoperative atrial fibrillation (POAF) affects 10 to 20% of noncardiac thoracic surgeries and increases patient morbidity and costs. The purpose of this study is to determine if preoperative CHA2DS2-VASc score can predict POAF after pulmonary lobectomy for nonsmall cell lung cancer.Methods Patients with complete CHA2DS2-VASc data who underwent lobectomies from January 2007 to January 2016 at a single institution were analyzed in a retrospective case–control study using a prospective database. An independent samples t-test was used to compare the mean CHA2DS2-VASc scores of POAF and non-POAF groups. A multivariable logistic regression analysis (MVA) evaluated the independent contribution of variables of the CHA2DS2-VASc score in predicting POAF. Chi-square test with univariate odds ratios (ORs) was used to determine a statistically significant cutoff score for predicting POAF.Results Of 525 total patients, 82 (15.6%) developed POAF (mean CHA2DS2-VASc score: 2.7) and 443 (84.4%) did not develop POAF (mean score: 2.3). Mean difference between these groups was significant at 0.43 (p = 0.01; 95% confidence interval [CI]: 0.09–0.76). In the MVA, significant predictors of POAF were age 65 to 74 years (adjusted OR [aOR] = 2.45; 95% CI: 1.31–4.70; p = 0.006) and age ≥75 years (aOR = 3.11; 95% CI: 1.62–5.95; p = 0.0006). Patients with CHA2DS2-VASc scores ≥5 had significantly increased OR for POAF (OR = 2.59; 95% CI: 1.22–5.50).Conclusions Preoperatively calculated CHA2DS2-VASc score can predict POAF in patients undergoing pulmonary lobectomy. Age is the most statistically significant independent predictor, and patients with scores ≥5 have significantly increased risk. Trials for POAF prophylaxis should target this population.
Keywords: thoracoscopy/VATS; lung cancer treatment; arrhythmia therapy; Maze; surgical ablation